Angiotensin-converting enzyme inhibitor fetopathy: long-term outcome. Issue 5 (6th February 2007) - Laube, Guido F; Kemper, Markus J; Schubiger, Gregor; Neuhaus, Thomas J
Abstract : Fetal exposure to angiotensin-converting enzyme inhibitors (ACEIs) is associated with increased neonatal morbidity and mortality. Long-term follow-up of three patients with fetal ACEI exposure revealed impaired renal function in two, severe hypertension and proteinuria in one and isolated polycythaemia in all three. Careful long-term follow-up of children with ACEI fetopathy is recommended.